2015
DOI: 10.1177/1065912915607638
|View full text |Cite
|
Sign up to set email alerts
|

Moving on Up? The Gendered Ambitions of State-Level Appointed Officials

Abstract: Many scholars have offered explanations as to why women are underrepresented at all levels of government. Conventional wisdom states that fewer women are in public office due to lower ambition, and that the presence of gendered perceptions among women considering elected office contributes to women’s disinterest in the political arena. Using original survey data, this article expands the theory of gendered perceptions to current state-level appointed officeholders to explain their levels of interest in pursuin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Practically speaking, women are more likely than men to begin their political careers in local or state offices (Palmer and Simon 2003; Sidorsky 2015; Scott 2018). This occurs primarily because men and women enter politics for different reasons.…”
Section: Religion Women-friendliness and State Legislative Represenmentioning
confidence: 99%
“…Practically speaking, women are more likely than men to begin their political careers in local or state offices (Palmer and Simon 2003; Sidorsky 2015; Scott 2018). This occurs primarily because men and women enter politics for different reasons.…”
Section: Religion Women-friendliness and State Legislative Represenmentioning
confidence: 99%
“…The board positions could be seen as an ineffective route to office. Alternatively, gendered perceptions of qualifications may keep women serving on state boards from expressing progressive ambition to run for state legislative office (Sidorsky 2015). Second, GBL itself could be ineffective at bringing more women onto state boards.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, Sidorsky surveyed appointed board members to explore progressive ambition of women appointed to state boards. She found that 38% of males and 33% of females are somewhat or very interested in pursuing elected office, suggesting some progressive ambition for board members (Sidorsky 2015). If state boards are a jumping point for women to run for higher state offices, and GBL inspires more women to join these boards, then we can expect more women to run for state office in states who passed GBL.…”
Section: Theoretical Expectationsmentioning
confidence: 99%